ANALYSIS OF UNMANNED AERIAL VEHICLE FORMATION FLIGHT CONTROL METHODS - Chepizhenko, Valery; Aliakin, Oleksii (Proceedings of National Aviation University, 2015)
The article explores different architectures, methods and approaches to control of unmanned aerial vehicles formation flight. We consider typical tasks and missions that require or may benefit from the use of multiple flight vehicles in a formation. In addition, we analyze advantages and disadvantages of each formation flight control method.